2005
DOI: 10.1186/1471-2369-6-8
|View full text |Cite
|
Sign up to set email alerts
|

Progression of kidney disease in type 2 diabetes – beyond blood pressure control: an observational study

Abstract: Background: The risk factors for progression of chronic kidney disease (CKD) in type 2 diabetes mellitus (DM) have not been fully elucidated. Although uncontrolled blood pressure (BP) is known to be deleterious, other factors may become more important once BP is treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
6
28
0
1
Order By: Relevance
“…Surprisingly, though, we found no significant differences in the prevalence of cardiovascular diseases and stroke between progressors and non-progressors, we believe that those patients who did not progress had been in longstanding advanced CKD stage (Table 2). Furthermore, in our study, systolic but not diastolic blood pressure was associated with increased progression of diabetic nephropathy, which is in accordance with previously published data 1119. This is likely due to the fact that type 2 diabetic patients primarily suffer from isolated systolic hypertension.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Surprisingly, though, we found no significant differences in the prevalence of cardiovascular diseases and stroke between progressors and non-progressors, we believe that those patients who did not progress had been in longstanding advanced CKD stage (Table 2). Furthermore, in our study, systolic but not diastolic blood pressure was associated with increased progression of diabetic nephropathy, which is in accordance with previously published data 1119. This is likely due to the fact that type 2 diabetic patients primarily suffer from isolated systolic hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…However, our study was not designed to evaluate treatment effects. The renoprotective effects of angiotensin II receptor blockers have been demonstrated in several clinical trials 711…”
Section: Discussionmentioning
confidence: 99%
“…Although it has already been reported that hypoalbuminemia was strongly associated with the severity of nephropathy in type 2 diabetic patients [1], there have been no reports on the association between serum albumin and the severity of other microvascular complica- tions, such as retinopathy and neuropathy, in diabetic patients. In the present study, we report two positive findings.…”
Section: Resultsmentioning
confidence: 97%
“…While evolutionary stability may suggest a critical role of the protein, only minor functions, generally related to transport of ions and drugs, of albumin have been documented. Although it has already been reported that hypoalbuminemia and proteinuria were strongly associated with the severity of nephropathy in type 2 diabetic patients [1], the association between serum albumin and the severity of other microvascular complications of diabetes, such as retinopathy and neuropathy and its clinical significance have not yet been elucidated. In addition, the relationship between the serum albumin and the presence of coronary artery disease in type 2 diabetic patients also remains unknown.…”
mentioning
confidence: 99%
“…This recommendation was primarily on basis of the findings of the Action to Control Cardiovascular Risk in Diabetes (27). In a retrospective observational study of patients with type II diabetes and CKD, BP was not a predictor of rate of decline of eGFR (28). Similarly, recent large analyses in predominantly nonproteinuric type II diabetes support a goal SBP of ,140 mmHg (29,30).…”
Section: Discussionmentioning
confidence: 99%